(untitled) (American & British Studies Annual, 2009)
The article focuses on ways Julian Barnes’s England, England presents the complexity of postmodern nostalgia, and explores the role nostalgic evocations of Christianity play in the novel’s problematisation of the relation between the present and the past. It is argued that contemporary nostalgia – also depicted in the Barnes’s novel - is heterogeneous, i.e., (1) it shows features of both a retreat from the present as well as reflection on the impossibility of such escape; (2) it allows for the ironisation of its desire to restore the lost thing or condition; (3) it maintains the interplay between irony and yearning, preventing irony from dominating the structure of contemporary nostalgia. In the article, the heterogeneous nostalgia in Barnes’s England, England is studied with the help of the concept of the Fall (and the related concepts of the pre- and postlapsarian) and of the metaphor of the arrested falling, crucial for one of Barnes’s characters. The article makes the ironically Christian colouring of the dynamics of nostalgia the basis for its reading of the Barnes’s novel.